(untitled) (Research, Society and Development, 2020)
The cultivation of different species promotes positive or negative changes in the chemical, physical or biological properties of the soil. In this context, this work aimed to evaluate the physical attributes of the soil and the organic matter levels in the Cerrado, under different cultivation systems. The treatments evaluated were the Cerrado sensu stricto, Cerrado in regeneration, eucalyptus and sugarcane, used entirely randomized design (DIC), with six repetitions in the ranges of depth 0-10, 10-20 and 20-40 cm. In all treatments analyses of organic matter, resistance to root penetration (RP) and aggregate index were performed. For the aggregate index in the soil, the geometric mean diameter (DMG) and weighted mean diameter (DMP) were considered. The treatments called Cerrado sensu stricto, Cerrado in regeneration and eucalyptus were those with the highest values of DMG and DMP and did not differ statistically in the ranges of 0-10 and 10- 20 cm depth. The organic matter in the soil in forest systems (LU, CR and EUC) contributes positively to the DMG and DMP indices, which results in an improvement in the soil physical structure. The lower PR observed in CA in the 0-10 cm layer is associated with soil development during planting, which justifies the low values of DMG and DMP found in this treatment. At depths of more than 20 cm, all treatments have critical values for PR, which can compromise the root system of deep cultures.